A Practitioner's Toolkit for Managing the Menopause. (October 2014) - Jane, F. M.; Davis, S. R.
Abstract Objective A number of learned societies, including the International Menopause Society, have produced position statements pertaining to the use of postmenopausal hormone therapy. These documents are highly informative but are not designed for use by primary-care physicians and nurse practitioners during routine consultations. Our aim was to produce a toolkit for practitioners that could be used during office consultations to assist them in the assessment and management of the menopause. Methods We used clinical experience in primary care, combined with published diagnostic algorithms, positions statements from learned medical societies and relevant peer-reviewed literature to develop assessment and management algorithms relevant to the primary care of women age 40 years and older. Results The resultant 'Practitioner's Toolkit for Managing the Menopause' comprises algorithms for the reasons why a woman might present, determination of menopausal status, key information that should be ascertained, issues that may influence treatment decision-making, hormonal and non-hormonal treatment options, symptom management and patient review, and a brief supporting document. Conclusions We believe these algorithms and supporting document provide an accessible desktop tool for health-care practitioners caring for women at midlife. The toolkit has been endorsed by the International Menopause Society for global use.